La protesizzazione nelle fratture laterali del femore prossimale - Benazzo, F.; Perticarini, L. (Lo Scalpello - Journal, 2018)
TOTAL HIP REPLACEMENT IN THE TREATMENT OF EXTRACAPSULAR HIP FRACTURESIn case of extracapsular hip fractures, whatever the anatomic type, internal fixation is currently the standardapproach. Hip conical modular implants are an excellent alternative to osteosynthesis in old patients with unstabletrochanteric fractures, rheumatoid arthritis or end-stage osteoarthritis with substantial hip symptoms before fracture,or like rescue procedure in the failure of osteosynthesis.